Secondary syphilis mimicking malignancy: A case report and review of literature. Issue 8 (August 2017) - Cerchione, Claudio; Maraolo, Alberto Enrico; Marano, Luana; Pugliese, Novella; Nappi, Davide; Tosone, Grazia; Cimmino, Ilaria; Cozzolino, Imma; Martinelli, Vincenzo; Pane, Fabrizio; Picardi, Marco
Abstract: A 56-year-old man developed disseminate lymphadenopathies, associated with hepato-splenomegaly, fever, nocturnal sweating and weight loss. Imaging studies in particular FDG-PET/CT raised the suspicion of a malignant disease. But blood flow cytometry assay for B/T cell clonality was negative and fine-needle biopsy of enlarged laterocervical lymph node showed a not specific " reactive hyperplasia ". Four months later, the patient developed a non-itching rash; since a further anamnestic investigation revealed an history of high-risk sexual intercourse, the patient underwent serological tests for Treponema pallidum that were positive at high titer, after a first negative screening. Made the diagnosis of secondary syphilis, the patient responded to the treatment with benzyl penicillin with complete resolution of symptoms. This case highlights the importance of carefully screening the patients with suspected lymphoadenopathies also for lue, particularly in presence of behavioral risk factors.